2022
DOI: 10.2174/1381612828666220310144500
|View full text |Cite
|
Sign up to set email alerts
|

MIR17HG: A Cancerogenic Long-Noncoding RNA in Different Cancers

Abstract: LncRNA MIR17HG, located at chromosome 13q31, plays an inevitable role in promoting tumor progressions, such as tumorigenesis, proliferation and metastasis. Besides, lncRNA MIR17HG is rare due to its open reading frame (ORF), which can be translated to produce protein. By systematically retrieval, we summarized that MIR17HG is an emerging lncRNA that exhibits carcinogenically in osteosarcoma (OS), glioma, cervical squamous cell carcinoma (CSCC), colorectal cancer (CRC), gastric cancer (GC), atypical teratoid rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, our study is the frst of its kind to demonstrate a considerable increase in serum MIR17HG levels in MM patients. Similarly, MIR17HG protein expression levels in meningiomas are higher than those in normal meningeal tissues [10], which further supports our fndings. Additional experimentation in our study revealed that the contents of clinical detection indexes Scr, β2-MG, LDH, calcium, IgG, and IgA were discernibly raised, while the contents of Hb and ALB were markedly lowered in MM patients, which are indicative of greater disease consumption and tumor burden.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To the best of our knowledge, our study is the frst of its kind to demonstrate a considerable increase in serum MIR17HG levels in MM patients. Similarly, MIR17HG protein expression levels in meningiomas are higher than those in normal meningeal tissues [10], which further supports our fndings. Additional experimentation in our study revealed that the contents of clinical detection indexes Scr, β2-MG, LDH, calcium, IgG, and IgA were discernibly raised, while the contents of Hb and ALB were markedly lowered in MM patients, which are indicative of greater disease consumption and tumor burden.…”
Section: Discussionsupporting
confidence: 87%
“…One such lncRNA, namely, MIR17HG, is located on chromosome 13q31 and plays an indispensable role in augmenting tumorigenesis, cancer cell proliferation, and tumor metastasis [9]. MIR17HG is universally overexpressed in osteosarcoma, cervical squamous cell carcinoma, glioma, colorectal cancer (CRC), and other tumors and further exerts carcinogenic efects in the process of carcinogenesis [10]. Intriguingly, lncRNA MIR17HG acts in a microRNA-and DROSAindependent manner and provides an important chromatin scafold for myeloma growth [11].…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, the deletion of either MYCN (type 1) or MIR17HG (type 2) seems to cause this type of disease ( de Pontual et al, 2011 ). MIR17HG generates six miRNAs, namely, miR-17, 18a, 19a, 20a, 19b-1, and 92a-1 ( Mendell, 2008 ), which have been reported to be involved in proliferation of various tumors ( Tan et al, 2022 ). MYCN protein seems to regulate the expression of these miRNAs by binding to the MIR17HG promoter region to upregulate miRNA expression ( de Pontual et al, 2011 ).…”
Section: Cytosolic Function Of Ncrnas In Brain Diseasesmentioning
confidence: 99%
“…Building on these results, we developed a new CRISPRi approach and identified MYC-regulated lncRNAs that are required for cell proliferation in human B cells [ 32 ]. Several of the top candidates of this CRISPRi screen are known for their involvement in cancer including DANCR [ 33 35 ], MIR17HG [ 36 ], SNHG17 [ 37 ] and SNHG26 [ 38 , 39 ]. Here, we have analyzed the function of the transcript ENSG00000254887, referred to as LNROP (long non-coding regulator of POU2F2), which was also identified in the previous CRISPRi screen as indispensable for B cell proliferation.…”
Section: Introductionmentioning
confidence: 99%